Conserved structural and dynamic aspects behind Ohr enzymatic catalysis: Ohr as potential drug targets - Domingos, Renato Mateus (2018)
Organic hydroperoxide resistance (Ohr) proteins are highly efficient thiol-based peroxidases that play central roles in bacterial response towards organic hydroperoxides. In Fungi, Ohr frequently presents a N-terminal extension, which is predicted to target them to mitochondria. The catalytic triad of Ohr comprises the peroxidatic Cys (Cp), the catalytic Arg (Rc) and a Glu (Ec) are fully conserved and interact among themselves by a salt bridge network in a reduced form of the enzyme (the so-called closed state). After getting oxidized to sulfenic acid (Cys-SOH), Cp condenses with the sulfhydryl group of resolution Cys (Cr) in a disulfide bond. The absence of negativity of the thiolate (RS-) in Cp facilitates the opening of the Arg-loop (containing the Rc) away from the active site, generating the so-called open state. However, the molecular events associated with the high reactivity of Ohr enzymes towards hydroperoxides and its specific reducibility by the dihydrolipoamide (DHL) or by lipoylated proteins were still elusive before this work. Additionally, several factors support the idea of Ohr as a target for drug development: (i) Ohr displays unique physicochemical properties; (ii) bacteria mutant for Ohr (Δ ohr) are highly sensitive to oxidative stress; (iii) the indications that Ohr might be involved in bacterial virulence; and (iv) its absence in mammals and vascularized plants. In this thesis, several aspects of Ohr enzymes were evaluated. In chapter 2, we biochemically characterized the Ohr homologs from the ascomycete fungus Mycosphaerella fijiensis Mf_1 (MfOhr), the causative agent of Black Sigatoka disease in banana plants, which presented extraordinary reactivity towards linoleic acid hydroperoxides (kobs = 3.18 (± 2.13) ×108 M-1.s-1). Furthermore, through subcellular fractionation of M fijiensis protoplast cells followed by western blot analysis, we confirmed the in silico prediction that MfOhr is a mitochondrial protein. In chapter 3 and 4, we described seven new crystallographic structures from two opportunistic pathogen, one from Xylella fastidiosa and six from Chromobacterium violaceum (including the first representative of the complex between Ohr and its biological reductant, DHL). Taken together these structures might represent new snapshots along the catalysis. Furthermore, several molecular modelling approaches, such as classical mechanics (MM), steered molecular dynamics (SMD), hybrid quantum mechanics (QM-MM) and together with enzymatic assays of point mutations, indicated that Ohr underwent unique structural switches to allow an intermittent opening (oxidized state) and returning to a more stable closed form (reduced state) of an Arg-loop along catalysis. Remarkably, dihydrolipoamide directly assisted the closing the Arg-loop and thereby the turnover of the enzyme. In chapter 5, we describe the identification of two compounds (C-31 & C-42) that could represent a framework for further studies attempting to find specific Ohr inhibitors, either through ab initio design of chemical compounds and virtual screening using pharmacophoric models. The IC50 calculated for C-31 and C-42 were 124.4-248.5 µM and 243.3-321.7 µM, respectively. Finally, this thesis highlights several new aspects related to Ohr function: 1 - evidence that eukaryotic Ohr are preferentially located in mitochondria and share several biochemical properties with the prokaryotic ones; 2 - the network of polar interactions among residues of the catalytic triad (Cp, Rc and E) strongly contributed to stabilize Ohr in the closed state, in an optimum configuration for hydroperoxide reduction; 3 - evidence that disulfide bond formation and the product release (alcohol derived from hydroperoxide reduction) facilitate the opening of the Rc loop to an intermediate state (probably not to the excessively open state presented in crystallographic structures); 4 - mapping the interactions between the biological reductant (DHL) and the Ohr active site; 5 - strong indications that DHL is not able to fit and react with Ohr in the close conformation; 6 - the first trials for search of molecules to specifically target Ohr proteins, although further assays must be performed to verify the specificity of the selected compounds to target Ohr. Therefore, we describe relevant new information for an antioxidant protein that displays highly efficient catalysis, comparable to other very important hydroperoxide removing enzymes, such as GSH peroxidase and peroxiredoxin